(untitled) (The Nepalese Management Review, 2024)
The intricate relationship between financial literacy and individual savings behavior has garnered considerable attention in personal finance. The study’s objective was to explore the effect of financial literacy, risk tolerance, education level, and work experience on the personal savings of university staff and their degree of relationship. Through a comprehensive survey (N=210), the collected data was subjected to correlational analysis, revealing significant positive correlations between financial literacy and personal savings (r = 0.623, p < 0.01). Further, a regression analysis was conducted, highlighting the predictive role of financial literacy (β = 0.585, p < 0.001), education level (β = 0.126, p < 0.05), and work experience (β = 0.124, p < 0.01) in determining personal savings behavior. These findings underscore the pivotal role of financial literacy in shaping prudent financial decisions and emphasize the potential for tailored educational interventions for enhanced financial well-being.